2014
DOI: 10.1155/2014/798535
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects ofBorago officinalisExtract on Amyloidβ-Peptide(25–35)-Induced Memory Impairment in Male Rats: A Behavioral Study

Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder and most common form of dementia that leads to memory impairment. In the present study we have examined the protective effects of Borago officinalis (borage) extract on Amyloid β (Aβ)-Induced memory impairment. Wistar male rats received intrahippocampal (IHP) injection of the Aβ(25–35) and borage extract throughout gestation (100 mg/kg). Learning and memory functions in the rats were examined by the passive avoidance and the Morris water maze (MWM) tasks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 48 publications
(58 reference statements)
1
28
0
3
Order By: Relevance
“…Many species of Boraginaceae family are grown in Iran and some of them are used in ethnomedicine [4] . However, there were no studies about their antiglycation properties and therefore, in the present study, we investigated the in vitro effects of aqueous and hydroethanol extracts of E. italicum, A. arvensis and T. incanum on albumin, hemoglobin, and crystalline glycation reactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many species of Boraginaceae family are grown in Iran and some of them are used in ethnomedicine [4] . However, there were no studies about their antiglycation properties and therefore, in the present study, we investigated the in vitro effects of aqueous and hydroethanol extracts of E. italicum, A. arvensis and T. incanum on albumin, hemoglobin, and crystalline glycation reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Some of these plants grow in Iran and used widely in Iran's folk medicine [2,3] . It has been reported that Borage (Borago officinalis L.) was useful for its antipyretic, antihypertensive, antispasmodic, aphrodisiac and diuretic properties [4,5] . Previous findings showed that some species of Boraginaceae were used for the treatment of hemorrhoids [6] .…”
mentioning
confidence: 99%
“…Estudos fitoquímicos mostraram que B. officinalis é composta por taninos, reninas, ácido ascórbico, beta-caroteno, niacina, riboflavina, ácido rosmarínico e flavonoides. Porém, é considerada como fonte de áci-do gama-linolênico, o qual possui efeitos benéficos no envelhecimento do cérebro, melhorando também a memória (37 É utilizada para regular o metabolismo e o sistema hormonal, indicada para amenizar sintomas da menopausa, como as ondas de calor. Ainda, é usada para aliviar e curar resfriados, bronquite e infecções respiratórias, por ter ação anti-inflamatória (36).…”
Section: Autor (Anounclassified
“…The solution was kept at room temperature for one week. Then, the extract filtered and the filtered solution was left at 37°C temperature for evaporation of alcohol and water in it (Ghahremanitamadon et al, 2014).…”
Section: Extractingmentioning
confidence: 99%